Efficacy and Tolerability of Lopinavir/Ritonavir- and Efavirenz-Based Initial Antiretroviral Therapy in HIV-1-Infected Patients in a Tertiary Care Hospital in Beijing, China - Su, Bin; Wang, Yin; Zhou, Ruifeng; Jiang, Taiyi; Zhang, Hongwei; Li, Zaicun; Liu, An; Shao, Ying; Hua, Wei; Zhang, Tong; Wu, Hao; He, Shenghua; et al. (Frontiers in Pharmacology, 2019)
Background: Lopinavir/ritonavir (LPV/r) is a major antiretroviral treatment in China, but little is known about the performance of first-line LPV/r-based regimen in treatment-naïve patients with human immunodeficiency virus type 1 (HIV-1) infection. This study aims to assess the efficacy and adverse effect events of LPV/r plus lamivudine and tenofovir or zidovudine as an initial antiretroviral treatment in HIV-1-infected individuals for whom cannot take efavirenz (EFV) or is allergic to EFV. Methods: We performed a retrospective study of patients registering with the China’s National Free Antiretroviral Treatment Program from July 2012 to January 2017, followed at a tertiary care hospital in Beijing, China. The primary outcome was the proportion of subjects with HIV-1 RNA ≤40 copies/ml at 6 and 24 months of treatment. We assessed the immunological response and adverse events. Results: In total, 4,862 patients were enrolled in the study and 237 were eligible for analysis in each study arm. During the first six months, virological suppression was better with the LPV/r-based regimen than with the EFV-based regimen (93.80 vs 87.80% for P < 0.05). Viral suppression rates continued to increase until 12 months, remain steady thereafter until 24 months, for both groups. The multilevel analysis revealed that patients in the LPV/r group were more likely to display improvements in CD4 T-cell count over time than those in the EFV group (P < 0.001). Grade 3 or 4 laboratory adverse events were observed in 14 patients (5.91%) from the LPV/r group and three patients (1.20%) in EFV group. Conclusion: Our findings demonstrate that LPV/r-containing regimens are effective and well-tolerated in Chinese treatment-naïve patients with HIV-1 infection.